¿Who is more aggressive? An analysis of hostility in medical students and its expression by gender - Tapia Varela, César Antonio; Tapia Varela, José Raúl; Ruiz Bernés, Salvador; Casillas Cueto, Juan Gabriel; Bañuelos Ramírez, Erika Jazmín (Acta Universitaria, 2026)
This quantitative, cross-sectional, and comparative study analyzed aggression levels among 638 medical students at a public university in Nayarit (59.2 % female; 40.8 % male) using the Buss-Durkee Hostility Inventory (BDHI). Due to the non-normal distribution of the data, Spearman and Kruskal-Wallis tests were employed for statistical analysis. The results revealed significant gender differences (p < 0.05): while men scored higher in physical aggression, women presented superior levels in verbal aggression, indirect aggression, irritability, guilt, and overall hostility scores. Furthermore, a moderate correlation between resentment and guilt was identified across both sexes. These findings challenge the traditional conception of aggression as a predominantly male trait, suggesting that within the medical academic context, women manifest higher levels of hostility in relational and verbal dimensions. This highlights the critical need for preventive interventions incorporating a gender-sensitive approach.